NEW DIMENSIONS OF CONSUMER WELFARE LEGISLATIONS IN INDIA VIS A VIS CONSUMER EDUCATION: AN ANALYTICAL STUDY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The emergence of the concept of welfare state  has influenced gradual development of the role  of the government for protecting the interests  of consumer’s. In Indian scenario the impact of  British rule has been to transform from duty  conscious society to the right conscious society.  Since Independence we have adopted the  concept of welfare state under new constitution  this has called for great intervention of state  protecting the rights and interests of consumers  as against strict adherence to caveat emptor  principle. In the end of the nineteenth century,  in the modern commercial age, the advancement  in the commercial transaction, standard form  of contract, globalisation brought an era of  consumerism where consumers started facing  exploitation by strong business class. In order  to maintain social harmony legal intervention  was called. By the end of nineteenth century  the Anglo American jurists had summarised the  whole jurisprudence upon the basis of rights  of contract duty base. Gradually the emphasis  was shifted from individual interests to social  interest. The emergence of the concept of welfare  state has influenced gradual development of the  role of the government for protecting the interests  of consumer’s. In the Indian scenario the impact  of British rule has been to transform from duty  conscious society to the right conscious society.  Since Independence we have adopted the concept  of welfare state under new constitution this has  called for great intervention of state protecting  the rights and interests of consumers as against  strict adherence to caveat emptor principle. Need  for protecting the interests of consumers also  felt in our country. Several laws for consumer’s  protection were there since 1947, but enactment  of consumer’s protection Act, 1986, and new  Amendment in 2002 gave more protection to  consumers. The enactment of Competition Act,  2002 by replacing of MRTP Act, 1969 brought  new dimensions to protection of consumer’s  interests in India.
Keywords: consumer education; concept of consumerism; consumer Protection Act; 1986; New Amendment Act; 2002; the competition Act; consumer protection Act; 2019